Dadas as funções reais de variável real $f(x) = mx + 1$ e $g(x) = x + m$, onde m é uma constante real com $0 < m <1$, considere as afirmações:

  1. $(f\circ g)(x) = (g\circ f)(x)$, para algum $x \in R$.

  2. $f(m) = g(m)$

  3. Existe $a \in R $ tal que $(f\circ g)(a) = f(a)$.

  4. Existe $b \in R$ tal que $(f\circ g)(b) = mb$.

  5. $0 < (g\circ g)(m) < 3$

Podemos concluir


img
ITA IIIT 30/12/2021 20:21
$• \ Afirmativa \ I:$ $\color{orangered}{Falsa}$ \begin{matrix} (f \circ g) \ (x) = m.(x+m) + 1 \\ (g \circ f) \ (x) = m.(x+1) + 1 \\ \\ m.(x+m) + 1 = m.(x+1) + 1 \\ \\ m = 1 \\ \color{gray}{\fbox{$0<m<1$}} \end{matrix} $• \ Afirmativa \ II:$ $\color{orangered}{Falsa}$ \begin{matrix} f(m) = m^2 + 1 \\ g(m) = 2m \ \ \ \ \ \ \\ \\ m^2 + 1 \ne 2m \end{matrix} $• \ Afirmativa \ III:$ $\color{orangered}{Falsa}$ \begin{matrix} (f \circ g) \ (a) = m.(a+m) + 1 \\ \ \ \ \ f(a) = m.a + 1 \ \ \ \ \ \ \\ \\ m=0 \\ \color{gray}{\fbox{$0<m<1$}} \end{matrix} $• \ Afirmativa \ IV:$ $\color{orangered}{Falsa}$ \begin{matrix} (f \circ g) \ (b) = m.(b+m) + 1 \\ \\ m.(b+m) + 1 = m.b \\ \\ m^2 = -1 \\ \color{gray}{\fbox{?}} \end{matrix} $• \ Afirmativa \ V:$ $\color{yellowgreen}{Verdadeira}$ \begin{matrix} (g\circ g) \ (m) = (m +m) + m \\ \\ 0<m<1 \\ 0<3m< 3 \\ \\ 0<(g\circ g) \ (m) < 3 \\ \\ \\ Letra \ (E) \end{matrix}
Modo de Edição
0 / 5000